TYPES OF RADIO PROGRAMM - Sotvoldiyeva Mokhlaroyim; Ulugbekov Odilbek (Galaxy International Interdisciplinary Research Journal, 2023)
The new medium had grown rapidly through the 1930s, vastly increasing both the size of its audience and its profits. In those early days, it was customary for a corporation to sponsor an entire half-hour radio program, placing its commercials at the beginning and the end. This is in contrast to the pattern which developed late in the 20th century in both television and radio, where small slices of time were sold to many sponsors and no corporation claimed or wanted sponsorship of the entire show, except in rare cases. These later commercials also filled a much larger portion of the total program time than they had in the earlier days.